The Killing of the Prophets: Unraveling a Midrash - Amaru, Betsy Halpern (Hebrew Union College annual, 1983)
Recent studies of Christianity such as Rosemary Ruether's Faith and Fratricide have examined the charge of "killing the prophets" within the context of the adversus Judaeos literature of the early Church. In contrast, this essay analyzes the Jewish midrashic tradition of propheticide as expressed in the stories of prophet killing which Moshe Hadarshan included in Midrash Aggada on Numbers 30:15. The eleventh century compiler briefly relates the stories of six prophet martyrs: Hur, Shemaiah, Ahijah, the Shilonite, Zechariah ben Yehoiada, Isaiah, and Jeremiah. The roots of five of these legends can be traced back to talmudic midrashim of the second century. The sixth, Jeremiah's martyrdom, is without roots in extant talmudic midrashim. However, close analysis of Hadarshan's midrash indicates a clear schematic structure which, if applied to existing midrashim on Jeremiah, would point to an early Jewish tradition regarding his martyrdom as well. Hadarshan's selection of martyrs and the pattern of themes found in this midrash indicate that the Jewish propheticide legends served several purposes. At one level they are simply efforts to deal with textual problems. At another, they reflect an attempt to comfort a martyred people and to set the tragedies of the first century within the context of rabbinic theodicy.